Brief Report About the Role of Hyperthermic Intraperitoneal Chemotherapy in a Prospective Randomized Phase 3 Study in Recurrent Ovarian Cancer From Spiliotis et al. Issue 2 (February 2017) - Harter, Philipp; Reuss, Alexander; Sehouli, Jalid; Chiva, Luis; du Bois, Andreas
Abstract : Abstract: A published so-called phase 3 study regarding HIPEC in ovarian cancer raised multiple questions. This commentary focusses on the weakness of the publication and discusses this in detail.